2023
DOI: 10.1109/tc.2022.3189578
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Thermal Covert Channel Attacks Based on Classification of Components of the Thermal Signal Features

Abstract: In response to growing security challenges facing many-core systems imposed by thermal covert channel (TCC) attacks, a number of threshold-based detection methods have been proposed. In this paper, we show that these threshold-based detection methods are inadequate to detect TCCs that harness advanced signaling and specific modulation techniques. Since the frequency representation of a TCC signal is found to have multiple side lobes, this important feature shall be explored to enhance the TCC detection capabil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…Machine learning has been used as a method to detect anomalies and classify whether processor activity is suspicious (i.e., the presence of a covert channel communication), particularly for cases where signal amplitudes are smaller and threshold-based techniques would not be sufficient, as described above [ 62 ]. It was found that TCC signals have multiple side lobes of high amplitudes that can be used for detection [ 66 ]. An artificial neural network classifier was developed and trained for TCC detection.…”
Section: Countermeasures Against Covert Channel Attacksmentioning
confidence: 99%
See 3 more Smart Citations
“…Machine learning has been used as a method to detect anomalies and classify whether processor activity is suspicious (i.e., the presence of a covert channel communication), particularly for cases where signal amplitudes are smaller and threshold-based techniques would not be sufficient, as described above [ 62 ]. It was found that TCC signals have multiple side lobes of high amplitudes that can be used for detection [ 66 ]. An artificial neural network classifier was developed and trained for TCC detection.…”
Section: Countermeasures Against Covert Channel Attacksmentioning
confidence: 99%
“…An artificial neural network classifier was developed and trained for TCC detection. The training data consisted of thermal signals over a period of 2 s, sampled at 1000 Hz, that were then transformed into the frequency domain (10 Hz to 500 Hz) with a discrete Fourier transform [ 66 ]. After training, this classifier was used during runtime to infer TCCs.…”
Section: Countermeasures Against Covert Channel Attacksmentioning
confidence: 99%
See 2 more Smart Citations